EATING VEGETABLES BEFORE CARBOHYDRATES DECREASE ENERGY INTAKE OF TYPE-2 DIABETES MELLITUS PATIENTS - Dian Eka Widyasari; Sugiarto -; Dono Indarto (Media Gizi Indonesia, 2022)
Diabetes mellitus is a non-communicable disease that has increased significantly in Indonesia and worldwide. Dietary arrangements through diet therapy are beneficial for improving the performance of the pancreas in producing and stimulating the work of insulin. This study aimed to determine the effect of the order of vegetable and carbohydrate consumptions on the decrease of energy intake. Method used randomized control trial with pre-post design.  A total of 24 people with non-complicating type-2 diabetes mellitus aged 18-65 years were assigned into 3 groups ; control group (C), vegetable before carbohydrate group (P1), and vegetable with carbohydrate group (P2) .  Energy intake before and after the intervention was measured using a 24-hour food recall. To compare pre-post intervention, paired T-test were used, meanwhile to compare difference among groups data were analysed using ANOVA.  A significant decrease in energy intake was found in P1 where the mean values of C and P1 were 17.75 ± 12.40 calories and 155.27 ± 23.40 calories (p < 0.001), and mean values of P1 and P2 were 155.27 ± 23.40 calories and 4.54 ± 48.99 calories (p < 0.001). The order of vegetable before carbohydrate consumption decreases energy intake of type-2 diabetes mellitus patients.